Answer:
![y^(-1)=√(9-x)\qquad where\ x\leq 9](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wn9kwfiooo3akt64mbm9qsl461xfdvscp0.png)
Explanation:
Given that y = 9 - x² where x ≥ 3 ⇒ y ≥ 0
To find the inverse, swap the x's and y's and solve for y inverse (y⁻¹)
![y = 9 - x^2\\\\x = 9 - (y^(-1))^2\\\\(y^(-1))^2 = 9 - x\\\\\sqrt{(y^(-1))^2} = √(9 - x)\\\\y^(-1)=\pm√(9-x)\qquad \text{Since y}\geq 0, \text{then the negative is not valid}\\\\y^(-1)=√(9-x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fnqbyyr2on3iqd5ulnb8lx2m85xl2dng7u.png)
The domain is the restriction on the x-values of the equation. Since the radicand (term under the square root symbol) must be greater than or equal to 0, then
9 - x ≥ 0
9 ≥ x ⇒ x ≤ 9